I Dissent : Ruth Bader Ginsburg Makes Her Mark - Levy, Debbie; Baddeley, Elizabeth (New York : Simon & Schuster Books for Young Readers, 2016)
Get to know celebrated Supreme Court justice Ruth Bader Ginsburg in the first picture book about her life.
Includes bibliographical references.
Keywords: Ginsburg, Ruth Bader -- Juvenile literature; Ginsburg, Ruth Bader; Judges -- Biography -- United States; Women judges -- Biography -- United States; Judges -- Biography; Women judges -- Biography; Women -- Biography